Alternative Technique for Class V Isolation of Resin-based Composite Restorations: A Case Report - Maan M. AlShaafi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Cervical lesions are increasingly more common in dental practice for many reasons, including high dietary sugar intake with oral hygiene neglect and a growing elderly population. Restoring a cervical lesion can be challenging due to its location, thus, making it a sensitive procedure. It is important not only to provide a quality restoration for the patient but also to eliminate the causative factor, whether by control of diet, increased water uptake for dry mouth, or improved oral hygiene habits, so that caries will not recur. This case report describes the clinical management of multiple cervical lesions, and the results thereof.